Timnewia García Aldrete (Psocodea: ‘Psocoptera’: Ptiloneuridae): new species and variation in the wing venation of T. jeaneae Silva-Neto, García Aldrete & Rafael - Da Silva-Neto, Alberto Moreira; Aldrete, Alfonso N. García; Barroso, Karen De Araújo; Rafael, José Albertino (Zootaxa, 2021)
A new species of Timnewia from the Brazilian state of Amazonas, is here described, illustrated and named as: Timnewia amazonense n. sp. This new species differs from T. greeni and T. jeaneae in details of the hypandrium and phallosome. New observations on variation in the forewing venation of T. jeaneae are also presented.